The comparison of Phytochemical Composition, Total Polysaccharides, and Highest Nutrient Content in Seaweed (Ulva lactuca) from Two Different Locations - Lailaturramadhini, Nova; Yuniarti, Ating; Maimunah, Yunita; Eka Supriatin, Febriyani; Suryanto, Damang; Ridwanudin, Asep (Department of Aquaculture, 2025)
Ulva lactuca is a source of structurally diverse and highly valuable bioactive compounds. Its chemical composition includes carbohydrates (up to 60%), proteins (10% - 47%), lipids (1% - 3%), and bioactive compounds such as polyphenols, which exhibit antibacterial, antiviral, antioxidant, and immunomodulatory properties. Ulvan, a heteropolysaccharide present in its cell walls, is known for its antiviral, antioxidant, and antimicrobial properties. This study aims to identify the potential of Ulva lactuca as a source of nutrition and health benefits. The research is descriptive-exploratory, aiming to analyze the phytochemical composition and total polysaccharides in Ulva lactuca from Ujung Genteng Beach, Sukabumi, West Java, and Lombok Beach, West Nusa Tenggara. The results indicate that the highest flavonoid content was found in the Ulva lactuca extract from Sukabumi, measuring 3.95 mg/L, compared to 3.686 mg/L in Ulva lactuca from Lombok. The alkaloid content in Ulva lactuca from Lombok was 26.53 mg/L, while in Ulva lactuca from Sukabumi, it was 24.78 mg/L. The highest tannin content was found in Ulva lactuca from Lombok at 9.87 mg/L, compared to 3.53 mg/L in Ulva lactuca from Sukabumi. The polysaccharide content in Ulva lactuca from Sukabumi was 50.83 mg/L, whereas it was 38.165 mg/L in Ulva lactuca from Lombok. Proximate analysis showed that Ulva lactuca from Lombok had a higher protein content (20.44%) compared to that from Sukabumi (15.47%).